Implementasi Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Matematika pada Materi Statistika di Kelas X-5 SMA Negeri 9 Surabaya - Diyah Ayu Safitri; Anik Kirana; Fitria Indahwati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study began with the problem of low Mathematics learning outcomes of class X-5 students of SMA Negeri 9 Surabaya, which were below the Minimum Completion Criteria (KKM) of 75. This study aims to improve the Mathematics learning outcomes of class X-5 students of SMA Negeri 9 Surabaya. This study is a classroom action research (PTK) conducted in two cycles in the 2023/2024 academic year with 37 students. The data collection method in this study used observation techniques. The instruments used were pretest and posttest questions. The results of the analysis showed that the application of the problem based learning (PBL) learning model succeeded in improving students' Mathematics learning outcomes in statistics material. Student learning outcomes increased from the pre-cycle to cycle I and to cycle II. Before the action, only 10 students achieved KKM with a classical completion percentage of 27.02%. In cycle I, the number of students achieving KKM increased to 26 with a classical completion percentage of 70.27%. In cycle II, the number of students achieving KKM increased again to 31 with a classical completion percentage of 88.57%.